Reducing American Exposure to Nitrate, Nitrite, and Nitroso Compounds: The National Network to Prevent Birth Defects Proposal - Black, Charles A. (Council for Agricultural Science and Technology (CAST), 1989)
This paper reviews the scientific literature on nitrates, concluding that there is inadequate evidence linking nitrate or nitrite ingestion to birth defects or to stomach cancer.